Digital Transformation as One of the Instruments for Overcoming the Public Health Crisis: The Role and Use of Ehealth Solutions during the Covid-19 Pandemic in Slovenia - Dalibor Stanimirović,; Matjaž Drev,; Živa Rant, (Medicine, Law & Society, 2022)
The comprehensive digital transformation of the Slovenian healthcare system and the use of national eHealth solutions would enable the citizens and healthcare professionals to access data and information relevant to highquality healthcare services, and healthcare managers to take evidence-based decisions and measures. This paper analyses the role and use of selected eHealth solutions during the Covid-19 pandemic in Slovenia. The pandemic has led to significant growth in interest in digital transformation processes and the use of eHealth solutions. It also breaks down the normative framework of eHealth and the compliance of eHealth solutions with the fundamental principles of information security and the General Data Protection Regulation. The study proceeded from a review of the literature, followed by discussions with experts engaged in managing eHealth solutions and an examination of current statistical data on the use of these solutions from administrator modules. The results of the study show that the Covid-19 pandemic could constitute a turning point in our understanding of digital transformation, which is becoming not only a key public health management instrument, but also an indispensable driver to further develop the healthcare system, and empower patients at times of national and international public health crises.
Keywords: digital transformation, public health, COVID-19, information security, eHealth